Drivers of international convergence in digital two-sided platform markets: The case of dominant business model components in online lending - Sabine Pur; Stefan Huesig; Christoph Schmidhammer (PLoS ONE, 2026)
Online lending marketplaces have emerged as potentially disruptive players in the financial industry by digitally connecting borrowers and lenders. However, little is known about the emergence of dominant business model patterns in this regulated, platform-based service industry. Drawing on dominant design theory, this study examines the international convergence of business model components in online lending since 2005. Using a comparative, longitudinal case study of the market leaders Funding Circle (the UK), LendingClub (the USA), and auxmoney (Germany), we analyze the Business Model Canvas components “customer segments” and “value propositions.” Our findings reveal a convergence toward peer-to-institution models, shaped by regulatory pressures, technological advances, and institutional capital. All marketplaces now address underserved borrower segments such as SMEs, the self-employed, and founders, while excluding retail investors. This indicates the emergence of internationally dominant business model components in potentially disruptive two-sided platform markets. We synthesize these findings into a generic, process-oriented model explaining how platform convergence unfolds across national contexts. This study extends dominant design theory to business models in regulated service industries and highlights external forces as key drivers of standardization. It offers practical insights for policymakers, institutional investors, and marketplace operators navigating scalability, regulation, and financial integration.